Application of modified and toughened admixtures in well cementing slurry: Progress and challenges - Zhang, Yihang (Frontiers in Materials, 2024)
Cementing, as an important part of the petroleum industry, plays a crucial role in ensuring the normal production and development of oil and gas resources. However, due to the brittle nature of Portland cement, it is prone to micro-cracks when subjected to downhole impact or vibration, which affects normal operations. Moreover, conventional elastic particles have a significant impact on the performance of cement paste, prompting people to continuously research new toughening admixtures. This article reviews the mechanism of toughening additives for oil well cement, the research status of physical toughening agents (fibers/whiskers, graphene) and polymer toughening agents (latex, epoxy resin, asphalt), aiming to provide reference and guidance for the development of new toughening additives.